Researching Children’s Experience Hermeneutically and Holistically (Alberta Journal of Educational Research, 2006)
This article is about the possibilities of conducting research with children productively. Children may need suitable prompts, occasions, or media for their expression. The discussion begins with an overview of the challenges or dynamics researchers can experience with any participants in qualitative research in the constructivist paradigm. It draws on key ideas from hermeneutics to clarify the importance of working holistically, attending to whole-part relationships, and having an increased sensitivity to language. Finally, two approaches are described and suggested as being helpful in research with children: the use of pre-interview activities and narrative approaches.